Pregnancy and implantation rates of egg donation, in one attempt - Roly, Hilario (2015)
Objectives: To determine pregnancy rates and implantation of the egg donation procedures in one go and comparison with results from other centers. Design: descriptive, retrospective study. Venue: Infertility and Reproduction procreate. Participants: Patients who underwent his first attempt with IVF Oocyte Donation. Interventions: Study of 26 patients who underwent their first attempt at IVF with ovulation 2005. The patients with pituitary suppression recibión menstruation day 21 of the previous cycle, endometrial then start preparing the first day of the cycle menstrual cycle synchronized controlled ovarian stimulation of the donor. It was signed informed consent in each case and use the spss12 program for analysis. Main outcome measures: Rate of pregnancy implantation. Results: 26 cycles of egg donation was reviewed. The average age was 41.7 ± 3.7 years (range 32-50 years), 20% under 40 and 80% greater than or equal to 40 years. Diagnoses were eight (30.8%) with physiological menopause, 17 (65.4%) low responder or diminished ovarian reserve and 1 (3.8%), congenital hereditary disease. Endometrial preparation lasted 21.7 ± 6.1 days (range 12-32 days), achieving an endometrial thickness of 11.9 ± 2.9 mm (range 8-19 mm). 11.8 ± 6.4 aspirated per donor eggs (range 4-24 eggs), fecundándose per patient 7.7 ± 4.4 eggs (range 3-18 eggs); in 2 patients it is frozen eggs, so that ICSI was performed. 2.8 ± 0.4 per patient was transferred embryos (range 2-3 embryos). Embryo transfer 24 cases (92.3%) was performed on day 3 and in 2 (7.7%) on day 5. A pregnancy rate of 65.4 (17/26) was achieved, with a rate implantation of 61.5% (16/26); 31.3% (5/16) were singleton pregnancy, 56.3% (9/16) twins and 12.5% (2/16) triple pregnancy. In the 2 cases with frozen fertilized eggs, there was no pregnancy. Conclusions: egg donation was a very effective technique, with pregnancy rate in one attempt to 65.4% clinical pregnancy rate of 61.5% and an implantation rate of 39.7%: up to 3 transferred embryos. Multiple pregnancy was high, requiring planning strategies to decrease without affecting the success rate.